Ambidentate bonding and electrochemical implications of pincer-type pyridylidene amide ligands in complexes of nickel, cobalt and zinc. Issue 36 (1st September 2020) - Melle, Philipp; Ségaud, Nathalie; Albrecht, Martin
Abstract : Pincer-type tridentate pyridyl bis(pyridylidene amide) (pyPYA2 ) ligand systems were coordinated to the Earth-abundant first row transition metals nickel, cobalt and zinc, revealing ambidentate N, N, N and O, N, O coordination behavior. Abstract : Pincer-type tridentate pyridyl bis(pyridylidene amide) (pyPYA2 ) ligand systems were coordinated to the Earth-abundant first row transition metals nickel, cobalt and zinc. A one-pot synthesis in water/ethanol afforded octahedral homoleptic bis-PYA complexes, [M(pyPYA2 )2 ](PF6 )2, whereas five-coordinate mono-PYA dichloride complexes, [M(pyPYA2 )Cl2 ], were obtained upon slow addition of the ligand to the metal chlorides in DMF. Electrochemical measurements further revealed a facile oxidation of the metal centers from Ni 2+ to Ni 4+ and Co 2+ to Co 3+, respectively, while the Zn 2+ system was redox inactive. These experiments further allowed for quantification of the much stronger electron donor properties of neutral N, N, N -tridentate pyPYA2 pincer ligands as compared to terpy. Remarkably, ortho -PYA pincer ligands feature amide coordination to the metal center via oxygen or nitrogen. This ambidentate ligand binding constitutes another mode of donor flexibility of the PYA ligand system, complementing the resonance structure dynamics established previously. NMR spectroscopic and MS analysis reveal that the meta -PYA ligand undergoes selective deuteration when coordinated to cobalt. This reactivity suggests the potential of this ligand as a transient proton reservoir for HX bond activation and, moreover, indicates the relevance of several resonance structures and therefore supports the notion that meta -PYA ligands are mesoionic.